2018
DOI: 10.1039/c7sm01106g
|View full text |Cite
|
Sign up to set email alerts
|

Purely-elastic flow instabilities and elastic turbulence in microfluidic cross-slot devices

Abstract: Strong extensional flows of viscoelastic fluids generate purely-elastic instabilities and elastic turbulence at high Weissenberg numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 31 publications
8
54
4
Order By: Relevance
“…By increasing the flow rate, we are able to change the Weissenberg number from 0.1 up to 200. Our results suggest that beyond a critical value of the Weissenberg number,Wi cr ≈ 0.46, the symmetry of flow is broken in agreement with previous studies (Arratia et al 2006;Sousa et al 2018). In the standard cross-slot geometry, figure 13 shows the flow distribution in symmetric Newtonian flows and a steady asymmetric flow for 190 ppm PAA in 70 : 30 glycerine-water viscoelastic fluid atWi = 0.8 and Re = 6 × 10 −6 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…By increasing the flow rate, we are able to change the Weissenberg number from 0.1 up to 200. Our results suggest that beyond a critical value of the Weissenberg number,Wi cr ≈ 0.46, the symmetry of flow is broken in agreement with previous studies (Arratia et al 2006;Sousa et al 2018). In the standard cross-slot geometry, figure 13 shows the flow distribution in symmetric Newtonian flows and a steady asymmetric flow for 190 ppm PAA in 70 : 30 glycerine-water viscoelastic fluid atWi = 0.8 and Re = 6 × 10 −6 .…”
Section: Resultssupporting
confidence: 88%
“…Previous experimental studies with the standard cross-slot geometry (Arratia et al 2006;Pathak & Hudson 2006;Haward et al 2012a;Sousa, Pinho & Alves 2018) have shown that by increasing the Weissenberg number to higher values, one can potentially trigger a second time-dependent instability. A numerical study of shear-thinning sPTT fluids conducted by Cruz et al (2016) has also shown that the critical values of Weissenberg number for the onset on instability for both the steady symmetry-breaking and the time-dependent instabilities are a function of the cross-section aspect ratio (AR = height/width) and the shear-thinning properties of the fluid (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Ref. [13] provides proof of the inequality and in experiments values of α = 3.3 − 3.5 [6,33] and α = 3 − 4 [34] have been observed. However, these values correspond to 3D geometries.…”
Section: B Power Spectral Density Of Velocity Fieldmentioning
confidence: 79%
“…Purely elastic instabilities manifest as spatiotemporal chaotic flow and elastic turbulence [3,4] in a wide range of natural and industrial applications: Elasticity generates secondary flows of DNA and blood suspensions in biological systems [5,6], hydrodynamic resistance increases [7] along with power consumption and cost in polymer processing, and elastic instabilities enhance mixing and dispersion in microfluidic and porous media flows [8][9][10]. Experimental [11][12][13][14][15] and numerical [16][17][18] efforts have characterized the onset and impact of elastic instabilities in well-defined geometries including cross slot [13,17], Couette [19,20], Poiseuille [8,21], and ordered pillar array flows [12,22,23]. In contrast to the high degree of symmetry in such systems, how geometrical disorder affects the onset of elastic instability remains an open question.…”
mentioning
confidence: 99%